Development of an elastothermoviscoplasticity damage model for injection molded short fiber reinforced thermoplastics with anisotropic damage evolutions. Issue 22 (17th November 2019) - He, Ge
ABSTRACT: This paper presents a finite deformation anisotropic and temperature-dependent constitutive model, which is developed for predicting elastoviscoplasticity and progressive damage behavior of injection molded short fiber reinforced thermoplastics (SFRPs) by the usage of the internal state variable (ISV) theory. In the present model, the SFRP is considered as an anisotropic single lamina and the viscoplasticity of the SFRP is captured with the help of three inelastic ISVs. A second-order damage tensor is introduced to model the evolution of the micro cracks/voids in the SFRP composites while also reflecting the anisotropic nature of the damage. The constitutive model developed herein arises employing standard postulates of continuum mechanics with the kinematics, thermodynamics, and kinetics being internally consistent. The developed model is then calibrated to the injection molded 35 wt% short glass fiber reinforced polyamide 6, 6 (designation PA66GF-35) with all material constants obtained by fitting the model to the experimental data. A parametric study is conducted on the model to numerically investigate the effects of strain rate, temperature, and fiber orientation effects on the elastoviscoplasticity and damage performance of such material.